Strategi Pemasaran Sayur Hidroponik (Studi Kasus CV. Metaya Ponik di Kota Sampit) - Pakpahan, Sartika (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The demand for hydroponic vegetables has been steadily increasing, necessitating the development of marketing strategies. This research aims to identify marketing strategies for CV. Metaya Ponik. This research employs a qualitative descriptive research approach through a case study, involving interviews, questionnaires, and direct observations of business owners. The study utilizes several analytical frameworks, including environmental analysis, IFAS and EFAS matrix analysis, and SWOT matrix analysis. The research results concerning internal and external factors reveal the following: 1) strengths with a score of 2.75, 2) weaknesses at 0.42, 3) opportunities at 2.92, and 4) threats at 1.44. The direction for the development policy of CV. Metaya Ponik falls under a Growth strategy, indicating that its strengths outweigh the opportunities.